2018
DOI: 10.1186/s12284-018-0240-3
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic analysis of the defense response to Magnaporthe oryzae in rice harboring the blast resistance gene Piz-t

Abstract: BackgroundRice blast (caused by Magnaporthe oryzae) is one of the most destructive diseases of rice. While many blast resistance (R) genes have been identified and deployed in rice cultivars, little is known about the R gene-mediated defense mechanism. We used a rice transgenic line harboring the resistance gene Piz-t to investigate the R gene-mediated resistance response to infection.ResultsWe conducted comparative proteome profiling of the Piz-t transgenic Nipponbare line (NPB-Piz-t) and wild-type Nipponbare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 30 publications
(44 reference statements)
0
19
0
Order By: Relevance
“…2). Similar to this present investigation, comparative proteome evaluation was also carried out with a single transgenic plant line in rice 2931 , soybean 32 , and maize 33 . Although the leaf morphology was not largely affected post 24 and 48 h of infection, the molecular signalling network was speculated to be altered for generating a novel leaf proteome.…”
Section: Resultsmentioning
confidence: 92%
“…2). Similar to this present investigation, comparative proteome evaluation was also carried out with a single transgenic plant line in rice 2931 , soybean 32 , and maize 33 . Although the leaf morphology was not largely affected post 24 and 48 h of infection, the molecular signalling network was speculated to be altered for generating a novel leaf proteome.…”
Section: Resultsmentioning
confidence: 92%
“…In our earlier studies, four proteins of a receptor-like protein kinase (gi|59,800,021), a NADP dependent malic enzyme (gi|54,606,800), a putative transaldolase (gi|57, 900,129), and a putative bowman birk trypsin inhibitor (gi|53,792,234), three C3HC4-type Ring finger E3 ubiquitin ligase (APIP2, 6, 10), and a bowman-Birk type bran trypsin inhibitor (APIP4) were confirmed to be involved in Piz-t-KJ201 interaction (Park et al 2012(Park et al , 2016Tian et al 2018;Zhang et al 2020). In the present study, we observed that a receptor-like protein kinase precursor (LOC_Os10g33040), a NADP-dependent malic enzyme (LOC_Os05g09440), a transaldolase (LOC_ Os08g05830), a bowman-Birk type bran trypsin inhibitor precursor (LOC_Os01g03360), and two zinc finger C3HC4 type domain containing protein (LOC_ Os01g20910 and LOC_Os12g04590) were also differentially regulated in Piz-t-KJ201 (Additional Table 2).…”
Section: Validation Of the Present Study By Comparing Previous Reportsmentioning
confidence: 99%
“…This gene was once widely used in breeding programs for increasing resistance to M. oryzae (Zhou et al 2006;Tian et al 2020). Numerous studies also have examined the interaction profiles of Piz-t-AvrPiz-t in rice (Park et al 2012(Park et al , 2016Wang et al 2016;Tang et al 2017;Tian et al 2018;Bai et al 2019;Zhang et al 2020). However, transcriptome profiling underlying the Piz-t-mediated rice resistance to blast fungus remains largely unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, an RLK was observed to be induced by M. oryzae inoculation in the NPB and NPB-Piz-t rice lines. In addition to PRs and RLKs, a putative bowman birk trypsin inhibitor, which might be involved in AvrPiz-t/Piz-t networks, was induced by M. oryzae infection in both compatible and incompatible interactions (Tian et al, 2018).…”
Section: Key Proteome Responses Underlying Rice Resistance To M Oryzaementioning
confidence: 99%